The Hormonal dysregulation and its consequences in Obese Women - overview - Katarzyna Maria Pala; Wiktoria Tomaszewska; Paweł Siudziński; Mateusz Łyko; Alicja Skoczylas; Maria Golińska; Anna Nowak; Jakub Kurasz; Wiktoria Podlasiewicz; Piotr Dudziak; Wojciech Maj (Journal of Education, Health and Sport)
Introduction